Diversity of endophytic fungi isolated from tree spinach (Cnidoscolus aconitifolius) (Euphorbiaceae) and their bioactivities - PRAPTIWI PRAPTIWI; KARTIKA DYAH PALUPI; MUHAMMAD ILYAS; LINA MARLINA; AHMAD FATHONI (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Praptiwi, Palupi KD, Ilyas M, Marlina L, Fathoni A. 2023. Diversity of endophytic fungi isolated from tree spinach Cnidoscolus aconitifolius (Euphorbiaceae) and their bioactivities. Biodiversitas 24: 6229-6239. Endophytic fungi associated with medicinal plants have been known as a reservoir for therapeutic compounds. Cnidoscolus aconitifolius I.M. Johns (Euphorbiaceae), which possesses several local names, including papaya jepang in Indonesia, has been historically used as traditional medicine. However, research on the bioactivity of endophytic fungi associated with it has yet to be conducted. The purposes of the study were to isolate endophytic fungi from C. aconitifolius and determine their bioactivity, i.e., antibacterial activity against Escherichia coli and S. aureus and free radical scavenging activity representing antioxidant activity. Identification of endophytic fungi was carried out based on their morphological characteristics. Total phenolic and flavonoid contents were determined by the spectrophotometric method. The qualitative antibacterial and antioxidant bioactivity screening was performed using the TLC-bioautography method. The quantitative analysis of antibacterial and antioxidant activity was conducted by microdilution to obtain IC50 and MIC values. In total, 14 endophytic fungal isolates were successfully isolated. Antioxidant analysis showed that one isolate had strong antioxidant activity, and one had moderate growth inhibition activity against E. coli. The total phenolic content strongly correlates with the AAI value as an indicator of antioxidant activity. The findings of this study reveal that Phomopsis PjBg-1, an endophytic fungus from C. aconitifolius, is identified as Phomopsis sp. LH243 possesses strong antioxidant activity and moderate antibacterial activity against E. coli. Endophytic fungi from C. aconitifolius have the prospect of being an alternative to antioxidants and antibacterials. The isolation of compounds responsible for bioactivities needs to be further studied.